Analisis Kausalitas Cranger Kebijakan Moneter Syari'ah Terhadap Perekonomian Indonesia - Tambunan, Khairina; Nawawi, Muhammad Ikhwanda (BISNIS, 2017)
This study aims to explain causality between Islamic monetary policy with Shariah Open Market Operation instrument and Bank Indonesia Sharia Certificate on inflation with time series data period from January 2010 - June 2017 which processed by Granger causality analysis method and using vectorautoregresive model. This study shows a direct causal relationship of OPTS to GDP, SBIS to OPTS and two-way causal relationship between SBIS and GDP.